Right-to-Repair, Product Durability and Obsolescence: A Legal Perspective - Smith, Robert Brian; Smith, Nucharee Nuchkoom (Universitas Negeri Semarang, 2024)
There is a growing global consensus on the need to enhance product durability as a response to increasing concerns about waste and consumer rights. Modern equipment, including motor vehicles, farm and construction machinery, and consumer goods, has become more sophisticated, making repairs more complex and costly. Manufacturers often restrict access to repair manuals, software updates, and spare parts, or design products in ways that impede easy repair. This article examines the interconnected concepts of the right to repair, product durability, obsolescence, and consumer rights protection. The European Union (EU) has emerged as a leader in consumer protection initiatives, introducing comprehensive measures addressing the right to repair and product durability. These initiatives have been widely adopted, either fully or partially, by nations across the globe. This study analyzes the EU's key legislative and regulatory approaches, concluding that they are highly consumer-centric and provide a valuable framework for other jurisdictions. However, one critical area requiring further attention is product recycling. The article emphasizes that manufacturers, sellers, and recycling companies should be held accountable for managing their waste domestically, adhering to the highest workplace safety and environmental standards. Governments are encouraged to promote the reuse of products and establish systems that facilitate repair and reuse activities. Additionally, the authors advocate for an expanded research program to enable large-scale industrial recycling of consumer waste, ensuring a more sustainable and circular economy. This study highlights the importance of a holistic approach to addressing product durability and repairability, advancing global consumer and environmental interests.